Intending war rightly: Right intentions, public intentions, and consent. Issue 4 (14th January 2016) - Grynaviski, Eric
Abstract: This article defends the normative status of the right intentions requirement in just war theory. Before we turn to many ethical questions about a conflict – whether there was just cause or whether a war was fought well – we often begin by asking whether the war was rightly intended. Particularly in the contemporary world, where questions of humanitarian intentions and their place in international law is an important political issue, clarifying what we mean by right intentions and showing why they matter is politically very important. Unfortunately, despite the importance of right intentions in the history of political thought, recent discussions give the concept mixed attention, leaving it obscure and difficult to apply. The first section reviews four traditional accounts, showing their underlying (and important) differences and respective weaknesses. The second section of the article argues that these models fail because they are rooted in private instead of public reason. A model of right intentions as public intentions is described and justified, where an intention is only right when the motives that underlie it can be endorsed by the group it is supposed to aid, and the opportunities it provides that group are endorsable by the intervener.